Potential DNA methylation biomarkers for the detection of clear cell renal cell carcinoma identified by a whole blood-based epigenome-wide association study - Hideki Ohmomo; Shohei Komaki; Yoichi Sutoh; Tsuyoshi Hachiya; Kanako Ono; Eri Arai; Hiroyuki Fujimoto; Teruhiko Yoshida; Yae Kanai; Koichi Asahi; Makoto Sasaki; Atsushi Shimizu (Epigenetics Communications)
Abstract Background Renal cell carcinoma (RCC) is the fourteenth most common cancer worldwide, accounting for approximately 4% of all cancers. More than 70% of RCC are clear cell RCC (ccRCC). To date, no reliable biomarkers for the detection of ccRCC have been identified. The aim of this study was to identify blood-based DNA methylation (DNAm) markers for the early detection and treatment of ccRCC. Results To identify ccRCC-associated DNAm markers, we performed targeted bisulfite sequencing (TB-seq) and an epigenome-wide association study (EWAS) using whole blood-derived DNA from 50 ccRCC patients and 50 healthy controls in the discovery phase. EWAS was performed using a linear regression model. The analysis was adjusted for age, sex, and the estimated cell-type composition. In the replication phase, the accuracy of the identified ccRCC-associated CpGs was verified in 48 independent ccRCC patients and 48 healthy controls. We identified six ccRCC-associated hypomethylated CpGs in PCBD2/MTND4P12 in the discovery phase (p < 1.75 × 10−8); four were reproducible in the replication phase (p < 2.96 × 10−8). The sum of the DNAm levels at the six CpGs was a valid indicator of ccRCC both in the discovery phase (area under the receiver operating characteristic curve [AUC-ROC] = 0.922) and in the replication phase (AUC-ROC = 0.871). Moreover, the results of cis-expression quantitative methylation analysis suggested that the DNAm levels of the ccRCC-associated CpGs affect the gene expression of transcription factor 7 (TCF7) and voltage-dependent anion-selective channel 1 (VDAC1), which are involved in cancer progression. Conclusions In this study, we identified six ccRCC-associated CpGs in PCBD2/MTND4P12 by EWAS using blood-based DNA. We found that the DNAm levels of the six CpGs in PCBD2/MTND4P12 may be a potential biomarker for early ccRCC detection, but the value as a biomarker needs to be investigated in future studies.